Productivity of Boran cattle and their Friesian crosses at Abernossa ranch, rift valley of Ethiopia. I. Reproductive performance and pre-weaning mortality - Haile-Mariam, M.; Banjaw, K.; Gebre-Meskel, T.; Ketema, H. (Springer, 1993)
Data collected on number of services per conception (NSC), age at first calving, (AFC), calving interval and calf pre-weaning mortality rate of Boran cattle and their Friesian crosses were evaluated. The NSC was 1.81, 1.61 and 1.69 for Boran, F1 Boran-Friesian and three-quarter Friesian heifers respectively. The AFC varied from 31.5 month in the F1 crosses to 46.8 months in the Boran heifers artificially inseminated with Friesian semen. The mean calving intervals were 465, 552, 525 and 487 days for Boran cows naturally mated to Boran and Friesian bulls, Boran and F1 cows artificially inseminated with Friesian semen, respectively. The pre-weaning calf mortality rate was 3.4% and was significantly influenced by parity, sex and interaction of breed with year of birth. Year as well as season had in general significant effects on the traits considered. However, the variation between mating or breeding groups was also large and it was in favor of the F1 crosses.